Pelatihan Mengkafani Jenazah Sesuai Syari’ah Di Kecamatan Tajur Halang - Fery Rahmawan Asma; Fajar Erlangga; Muhammad Soleh Ritonga (CV. Multi Kreasi Media, 2026)
Embalming a corpse is a matter that must be handled promptly. Therefore, it is important for all Muslims to know about it. Although shrouding a corpse is a fardhu kifayah (obligatory duty) in Islam, there is a great reward for a Muslim who cares for others, including caring for the corpse, as not all Muslims are willing to know or even participate in it. Therefore, the knowledge of the congregation of the prayer room or mosque needs to be continuously updated and even honed so that they fully understand the steps and procedures involved in shrouding a corpse, from preparing the cloth to tying it. This community service activity was carried out through interactive module presentations interspersed with questions and answers, and concluded with independent group practice. The implication of this training was the formation of the musholla Al-Jihad care group, which specifically handles Muslim corpses in the Grand Mulia Kalisuren Housing Complex.